The immune carrier properties of acid-treated Salmonella Minnesota R595 bacteria - Bellstedt, D. U.(Dirk Uwe) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1988.